Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Pada PT. Chitose Internasional, Tbk Periode Tahun 2015-2019 - Novita Wulandari; Indri Ayu Tansar; Boy Suzanto (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
One of the ways a company can increase capital is through debt or increasing the number of ownership by listing its shares on the capital market. Thus, this study verifies the effect of profitability and leverage on firm value in one of the companies listed on the Indonesia Stock Exchange. The quantitative method uses to determine the magnitude of the effect of profitability and leverage on value during the 2015-2019 period. The results showed that profitability had a positive and significant effect, while leverage had a negative effect on firm value. However, simultaneously profitability and leverage have a significant effect on firm value. The study results indicate that it is necessary to increase sales and pay attention to the amount of debt and the risks caused. When the amount of debt exceeds their capital, investors will hesitate to remember the risks the company has.